ANALISIS PENGARUH PENERAPAN AKUNTANSI MANAJEMEN LINGKUNGAN DAN STRATEGI TERHADAP INOVASI PRODUK DAN INOVASI PROSES (Studi Empiris pada Perusahaan Manufaktur yang terdapat di Provinsi Riau) - Ayu Rahayu; Ria Nelly Sari; Al Azhar L ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
Increased awareness regarding environmental issues has encouraged organizations to use environmental management accounting, which has been said to deliver many benefits to users, including an increase in innovation. This study aims to examine the effect of the implementation of environmental management accounting and strategy of the company’s innovation. That innovation is product innovation and process innovation. Using survey data from management accountans manufacturing company located in Province Riau. The sample used is manufacturing company’s located in Province Riau. The sample used some 30 large-scale manufacturing firms in Province Riau. The analytical method used is with the help of sofware Smart PLS. Parameter Significant tested by comparing the value tstatistic with ttable, where the value tstatistik>ttabel at 0,05 confidence level, its meaning there significant influence between independent variabel with dependent variabel. The result indicate that there is a positive effect between prospector strategy with environmental management accounting at tstatistic value 6,409. Environmental management accounting use has a positive effect with process innovation at tstatistic value 3,249, but not with product innovation at tstatistic value 1,113. Prospector strategy has a positive effect with product innovation at t statistic value 6,109, but not with process innovation at tstatistic value 0,687.Keywords: environmental accounting management, strategy, and innovation.